Contemporary art from the Middle East : regional interactions with global art discourses - Keshmirshekan, Hamid (International library of modern and contemporary art, 2015)
How is home-grown contemporary art viewed within the Middle East? And is it understood differently outside the region? What is liable to be lost when contemporary art from the Middle East is 'transferred' to international contexts - and how can it be reclaimed? This timely book tackles ongoing questions about how 'local' perspectives on contemporary art from the Middle East are defined and how these perspectives intersect with global art discourses. Inside, leading figures from the Middle Eastern art world, western art historians, art theorists and museum curators discuss the historical and cultural circumstances which have shaped contemporary art from the Middle East, reflecting on recent exhibitions and curatorial projects and revealing how artists have struggled with the label of 'Middle Eastern Artist'. Chapters reflect on the fundamental methodologies of art history and cultural studies - considering how relevant they are when studying contemporary art from the Middle East - and investigate the ways in which contemporary, so-called 'global', theories impact on the making of art in the region. Drawing on their unique expertise, the book's contributors offer completely new perspectives on the most recent cultural, intellectual and socio-political developments of contemporary art from the Middle East.